RETRACTED: Protective Effect of Xinmailong Injection on Rats With Myocardial Infarction - Zhang, Wei; Li, Kailiang; Ding, Yu; Ren, Jiefeng; Wang, Haijun; Si, Quanjin (Frontiers in Physiology, 2021)
This study aimed to investigate the protective effect of Xinmailong injection on rats with myocardial infarction. Thirty-six rats were induced myocardial infarction by operation, and six underwent sham operation. The myocardial infarction rats were randomly divided into 3 groups,12 in each, and administered intraperitoneal injection of Xinmailong 5 mg/(kg·d), sodium creatine phosphate 80 mg/(kg·d) or normal saline as control respectively for 14 days. When the treatments were completed, the hemodynamic parameters of the rats were observed, and blood samples were taken to examine blood routine, blood coagulation index, liver and kidney function, inflammatory index, myocardial marker, thrombo-elastography, and other indicators. The morphology of cardiomyocytes was observed through light microscopy, and the microstructure of the myocardial cells was observed under electron microscope. No significant difference was found in blood routine, liver and kidney function, and blood coagulation index between the Xinmailong and sodium creatine phosphate groups compared with the saline control group. However, the inflammatory index and levels of myocardial markers were significantly decreased, and cardiac function were significantly improved. In terms of the morphology of myocardial cells, the Xinmailong group was similar to the sodium creatine phosphate group, the myocardial cell membrane was protected, and myocardial cell damage was reduced. In conclusion, Xinmailong is safe and had anti-inflammatory, heart-improving, and myocardial-protective effects. Its effectiveness is not inferior to that of sodium creatine phosphate.